Development of Religious Tourism Potential to Increase Community Income in Wetland Areas in Tapin Regency - Maryono Maryono; Siswanto Rawali (Universitas Lambung Mangkurat, 2024)
A tourism potential that has always been developing up until now is religious tourism, which has had a positive impact on communities in wetland areas. This study aims to analyze the potential of religious tourism as an effort to increase community income in wetland areas in Tapin Regency. This is qualitative research with data obtained through observation, interviews and documentation, and data analysis using SWOT analysis. The results have shown that according to the identification of internal and external factors depicted in the diagram, there is a very good potential for religious tourism in the Tapin Regency. The development of religious tourism objects may improve the community's economy through job creation with the growth of small business sectors or the opportunity to work as security officers, parking attendants, and cleaners. Policy recommendations that can be implemented are aggressive strategies of Strengths (S) and Opportunities (O), although religious tourism objects in Tapin Regency may have some weaknesses and sufficient threats, these religious tourism objects can take advantage of existing strengths and opportunities for them to survive and develop optimally. The presence of tourists around religious tourism objects has been able to increase the income of people around religious tourism objects located in wetland areas in Tapin Regency.